Analyzing the issues of asymmetry in the strength of fencers bodies and the effectiveness of combining Aerobics with Fencing on their muscles by a new sport AeroFencing: - Esfanjani, Mina; Faress, Fardad; Esfanjani, Mitra (Technium Education and Humanities, 2022)
This paper attempts to introduce Aerofencing as a young kind of sport in which athletes perform combining rhythmic choreography with footwork and handwork of fencing with elements of aerobic and aerobic dance to music. Additionally, it reports the results of an experiment that aimed to combine aerobic exercise and fencing as a new field called AeroFencing for improving asymmetric fencing exercise and helping reduce injuries. Fencers from the experimental group underwent four-week AeroFencing training, while those from the control group underwent regular fencing training. The fencers' performance was analyzed two times: before the practical training (pretest)and after four weeks of training (posttest) in the Columbus Fencing & Fitness. Participants passed three tests that just studied the anaerobic power and speed of the dominant and non-dominant sides of the body. The fencers from the experimental group generally performed better in posttests than in pretests. The results showed that the training protocol of the present study caused a significant improvement in the anaerobic power, hand speed at the time of the attack, and leg speed of the participants in the experimental group compared to the control group.